Business letter writing made simple - Rosenthal, Irving; Rudman, Harry W. (Mandaluyong City : National Book Store, Inc., 1955)
This book has been prepared to provide reliable and authoritative guidance in all matters relating to business letter writing...
Chapter One: Business letter writing today and yesterday 17 -- Chapter Two: Appearance and structure of the business letter 22 -- Chapter Three: The Sales letter 38 -- Chapter Four: Direct-mail sales letters 52 -- Chapter Five: Credit letters 78 -- Chapter Six: Collection letters 90 -- Chapter Seven: Employment letters 108 -- Chapter Eight: Complaints and adjustments 120 -- Chapter Nine: Miscellaneous letters 133 -- Chapter Ten: Post cards and telegrams 151
Keywords: BUSINESS LETTERS